Inclusive Access to Anti-Hoax Websites: A Comprehensive Examination of User Experiences among Persons with Disabilities in Indonesia - Rahmatul Furqan; Shabrina Syntha Dewi (Information Technology Education Journal, 2025)
In an era of digital misinformation, the role of anti-hoax websites in disseminating accurate information is crucial. However, ensuring that these platforms are accessible to all users, including those with disabilities, remains a challenge. This research delves into the accessibility landscape of Indonesian anti-hoax websites, focusing on inclusivity for persons with disabilities (PwD) in accordance with WCAG 2.1 guidelines. The two selected websites for evaluation are prominent in the Indonesian context: "Turn Back Hoax" (www.turnbackhoax.id) and the official anti-hoax page managed by the Ministry of Communication and Information in Indonesia (www.kominfo.go.id). Additionally, this study aligns with the gratification theory in communication, which emphasizes that accessible websites lead to a higher level of gratification for all users. An automated evaluation tool known as SortSite is utilized to facilitate the identification of accessibility barriers and offers insights into areas of improvement. In addition to automated evaluations, this study incorporates in-depth interviews with PwD to gain insights into their firsthand encounters with these websites. Their perspectives provide valuable qualitative insights into the challenges they face and the areas where improvements are needed. Our research emphasizes the need for anti-hoax websites to prioritize accessibility. This research underscores the necessity of extending accessibility considerations beyond the scope of misinformation and highlights the ongoing journey toward a more inclusive digital landscape.